Risk factors for unplanned pregnancy among young women in Tanzania. Issue 4 (31st July 2013) - Calvert, Clara; Baisley, Kathy; Doyle, Aoife M; Maganja, Kaballa; Changalucha, John; Watson-Jones, Deborah; Hayes, Richard J; Ross, David A
Abstract : Background: With effective contraceptives available, unplanned pregnancies are preventable and educational interventions have been cited as a promising platform to increase contraceptive use through improving knowledge. However, results from trials of educational interventions have been disappointing. In order to effectively target future interventions, this study aimed to identify risk factors for unplanned pregnancy among young women in Mwanza, Tanzania. Methods: Data were analysed from the MEMA kwa Vijiana Trial Long-term Evaluation Survey, a cross-sectional study of 13 814 young adults aged 15–30 years in Mwanza, Tanzania. Potential risk factors for unplanned pregnancy were grouped under three headings: socio-demographic, knowledge of and attitude towards sexual health, and sexual behaviour and contraceptive use. Conditional logistic regression was used to identify predictors of reported unplanned pregnancy among all sexually active women. Results: Increasing age, lower educational level, not being currently married, knowing where to access condoms, increasing number of sexual partners and younger reported age at sexual debut were associated with unplanned pregnancy. Discussion: A number of demographic and sexual behaviour risk factors for pregnancy are identified which will help guide future intervention programmes aiming to reduce unplanned pregnancies. This study suggests effective measures to prevent unplanned pregnancies should focus on encouraging girls to stay in school.